2014
DOI: 10.1016/j.juro.2014.05.096
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Different Phenotypes of Interstitial Cells in the Upper and Deep Lamina Propria of the Human Bladder Dome

Abstract: To our knowledge this is the first study of 2 main interstitial cell populations in the upper and deeper lamina propria of the human bladder with distinct ultrastructural and immunohistochemical phenotypes. Future research is needed to elucidate whether these morphological findings reflect different roles for upper and deeper lamina propria interstitial cells in bladder physiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 30 publications
7
65
0
Order By: Relevance
“…the area between the urothelium and detrusor smooth muscle) and IC in the detrusor [4] (inter-and intramuscular). Having been reported in bladders from different species including rat [5], guinea pig [4,6], mouse [7] and human beings [8], these two IC populations appear to be a constant, species-independent finding. Functional data on bladder IC are still limited, and the general hypothesis is that LP IC might be involved in non-neural sensory signal transduction from the urothelium towards the detrusor muscle, while detrusor IC might have a role in pacemaking and/or transduction of pacemaking signals in the detrusor area [3].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…the area between the urothelium and detrusor smooth muscle) and IC in the detrusor [4] (inter-and intramuscular). Having been reported in bladders from different species including rat [5], guinea pig [4,6], mouse [7] and human beings [8], these two IC populations appear to be a constant, species-independent finding. Functional data on bladder IC are still limited, and the general hypothesis is that LP IC might be involved in non-neural sensory signal transduction from the urothelium towards the detrusor muscle, while detrusor IC might have a role in pacemaking and/or transduction of pacemaking signals in the detrusor area [3].…”
Section: Introductionmentioning
confidence: 79%
“…Several authors also reported on the absence of the typical ultrastructural ICC characteristics in IC in the bladder, lending additional evidence for another phenotype for these cells [8,18,19]. We know from previous work that IC in the bladder constitute a complex cell family including fibroblasts, myofibroblasts, ICC-like cells and telocytes, with different IC phenotypes in the lamina propria versus the detrusor [8,18,19]. At present, our knowledge of Lower panels: immunohistochemical stains for KIT on guinea pig bladder and gut with clone A4502.…”
Section: Kitmentioning
confidence: 89%
“…The role this compact subepithelial layer has received considerable attention lately, having been proposed to modulate afferent discharge and sensations [10, 11]. Whether these cells are ICs with a different phenotype [30] or fibroblasts with myoid differentiation, given the expression of α -smooth muscle actin [34], awaits further investigations. In the present study, these suburothelial ICs in the bladder and urethra were not affected by either CYP or Imatinib treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence of 2 main interstitial cell populations in the upper and deeper lamina propria in the human bladder dome region, which have distinct ultrastructural and immunohistochemical phenotypes [20]. This differentiation in detrusor muscle development and ultrastructural composition may play a role in the pathophysiology associated with IC.…”
Section: Discussionmentioning
confidence: 99%